Role of Transcription in the Temporal Control of Development in Caulobacter crescentus - Newton, Austin (1972)
The requirement for transcription during development of the stalked bacterium, Caulobacter crescentus, was studied with synchronous cultures of swarmer cells. The developmental pattern in these bacteria was first established by determination of the times at which specific changes in cell structure and function occurred. These changes could be divided into those characteristic of (a) development of the swarmer cell into the stalked cell: loss of motility and synthesis of the stalk, and (b) development of the stalked cell into the asymmetric dividing cell: chromosome replication, synthesis of the flagellum, motility, and division. The effect of rifampin in blocking several of these steps—loss of motility, initiation of chromosome replication, and cell division—indicates that RNA synthesis is required throughout the cell cycle for normal differentiation.